2011
DOI: 10.1088/2041-8205/727/2/l31
|View full text |Cite
|
Sign up to set email alerts
|

HST WFC3/IR OBSERVATIONS OF ACTIVE GALACTIC NUCLEUS HOST GALAXIES AT z ∼ 2: SUPERMASSIVE BLACK HOLES GROW IN DISK GALAXIES

Abstract: We present the rest-frame optical morphologies of active galactic nucleus (AGN) host galaxies at 1.5 < z < 3, using near-infrared imaging from the Hubble Space Telescope Wide Field Camera 3, the first such study of AGN host galaxies at these redshifts. The AGN are X-ray selected from the Chandra Deep Field South and have typical luminosities of 10 42 < L X < 10 44 erg s −1 . Accreting black holes in this luminosity and redshift range account for a substantial fraction of the total space density and black hole … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
206
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(229 citation statements)
references
References 34 publications
19
206
3
1
Order By: Relevance
“…It seems that AGN evolution is dominated by a nonmerger process. Other studies about AGN hosts reach similar conclusions, such as Kocevski et al (2012), Santini et al (2012), and Schawinski et al (2011). Their results provide evidence that the starburst galaxies only account for 10% of the cosmic SFR density at z ∼ 2 (Rodighiero et al 2011;Lamastra et al 2013).…”
Section: Introductionsupporting
confidence: 64%
“…It seems that AGN evolution is dominated by a nonmerger process. Other studies about AGN hosts reach similar conclusions, such as Kocevski et al (2012), Santini et al (2012), and Schawinski et al (2011). Their results provide evidence that the starburst galaxies only account for 10% of the cosmic SFR density at z ∼ 2 (Rodighiero et al 2011;Lamastra et al 2013).…”
Section: Introductionsupporting
confidence: 64%
“…The possibility of a higher incidence of powerful radio sources associated with disk galaxies at high-z has been brought up by Norris et al (2008), although they have so far identified only one possible candidate in their deep field. More recently, Schawinski et al (2011) have studied the optical morphologies of host galaxies of AGN at 1.5 < z < 3 X-ray selected (10 42 < L X < 10 44 erg s −1 ) in the CDF-S. The majority of these AGN are hosted by disk galaxies consistent with what is found for Seyfert galaxies in the local Universe (see also Cisternas et al 2011).…”
Section: Radio Sources Like Pks 1814-637: How Rare?mentioning
confidence: 54%
“…Using the deep VLA radio observation presented by Mainieri et al (2008), we find that two of the AGN selected by Schawinski et al (2011) appear to have radio counterparts of 3.7 and 0.07 mJy at 1.4 GHz. These sources are both at z ∼ 1.6 and converting this to radio luminosity, these sources have a radio power of log P 1.4 GHz = 25.6 W/Hz and 24.1 W/Hz respectively.…”
Section: Radio Sources Like Pks 1814-637: How Rare?mentioning
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, recent observations of AGN host morphologies and colors have suggested that major mergers probably do not fuel most low and intermediate-luminosity AGN, as a large fraction appear in "normal" disks (Gabor et al 2009;Schawinski et al 2011;Cisternas et al 2011;Kocevski et al 2012;Rosario et al 2011;Civano et al 2012;Santini et al 2012;Mullaney et al 2012;Treister et al 2012). This should perhaps not be surprising.…”
Section: Introductionmentioning
confidence: 99%